Effect of Entrepreneurship Education and Self Efficacy Towards The Intention of Entrepreneurship - Patricia Martyajuarlinda; Djoko Dwi Kusumajanto (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2018)
This study aims to know the influence of entrepreneurship education and self efficacy toward student’s  intention of entrepreneurial. The population in this study was 140 students of grade XII marketing and accounting for Islamic Vocational High School with a sample of 104 students. The method of data collection in this study used questionnaires and documentation. This research is a quantitative study, using descriptive analysis, multiple linear regression analysis, and classic assumption tests which include normality, multicollinearity, and heteroscedasticity tests. Based on the result, entrepreneurship education and self efficacy show a significant influence on student’s  intention of entrepreneurial at SMK Islam Batu.